Characterization of the chloroplast genome of Lonicera ruprechtiana Regel and comparison with other selected species of Caprifoliaceae - Gu, Lei; Hou, Yunyan; Wang, Guangyi; Liu, Qiuping; Ding, Wei; Weng, Qingbei (PloS one, 2022)
Lonicera ruprechtiana Regel is widely used as a greening tree in China and also displays excellent pharmacological activities. The phylogenetic relationship between L . ruprechtiana and other members of Caprifoliaceae remains unclear. In this study, the complete cp genome of L . ruprechtiana was identified using high-throughput Illumina pair-end sequencing data. The circular cp genome was 154,611 bp long and has a large single-copy region of 88,182 bp and a small single-copy region of 18,713 bp, with the two parts separated by two inverted repeat (IR) regions (23,858 bp each). A total of 131 genes were annotated, including 8 ribosomal RNAs, 39 transfer RNAs, and 84 protein-coding genes (PCGs). In addition, 49 repeat sequences and 55 simple sequence repeat loci of 18 types were also detected. Codon usage analysis demonstrated that the Leu codon is preferential for the A/U ending. Maximum-likelihood phylogenetic analysis using 22 Caprifoliaceae species revealed that L . ruprechtiana was closely related to Lonicera insularis . Comparison of IR regions revealed that the cp genome of L . ruprechtiana was largely conserved with that of congeneric species. Moreover, synonymous (Ks) and non-synonymous (Ka) substitution rate analysis showed that most genes were under purifying selection pressure; ycf3 , and some genes associated with subunits of NADH dehydrogenase, subunits of the cytochrome b/f complex, and subunits of the photosystem had been subjected to strong purifying selection pressure (Ka/Ks < 0.1). This study provides useful genetic information for future study of L . ruprechtiana evolution.